2019
DOI: 10.1007/s11469-019-00151-9
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Depression in the Relationship Between Body Image Dissatisfaction and Cyberbullying Perpetration

Abstract: Preliminary evidence suggests that psychopathological factors (e.g., depression) are associated with higher engagement in cyberbullying perpetration, and those with elevated body image dissatisfaction (BID) are more susceptible to depression. However, the possible impact of body image dissatisfaction (BID) on cyberbullying remains untested. The present study examined the direct and indirect relationships of BID with cyberbullying via depression among a sample of 507 university students (mean age, 21.37 years; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…There is a consistent relationship across studies between cyberbullying and depression among children and adolescents [ 30 , 181 ]. Short sleep duration has been associated with increased digital time among adolescents [ 35 ] and social media overuse with poor sleep outcomes: (i) sleep disruption (melatonin suppression) and desynchronization of body clock–hormone imbalance and brain inflammation and lower levels of deep sleep, (ii) desensitization of the brain reward system (reward, focus and motivation), and (iii) exposure to light at night has also been associated with risk of depression [ 28 , 182 , 183 ].…”
Section: Discussionmentioning
confidence: 88%
“…There is a consistent relationship across studies between cyberbullying and depression among children and adolescents [ 30 , 181 ]. Short sleep duration has been associated with increased digital time among adolescents [ 35 ] and social media overuse with poor sleep outcomes: (i) sleep disruption (melatonin suppression) and desynchronization of body clock–hormone imbalance and brain inflammation and lower levels of deep sleep, (ii) desensitization of the brain reward system (reward, focus and motivation), and (iii) exposure to light at night has also been associated with risk of depression [ 28 , 182 , 183 ].…”
Section: Discussionmentioning
confidence: 88%
“…A six-year longitudinal study indicated that negative mental factors positively predicted cyberbullying perpetration ( You and Lim, 2016 ). Several studies have also confirmed a significant correlation between negative emotions and cyberbullying perpetration ( Balta et al, 2020 ; Schodt et al, 2021 ). Accordingly, the following hypothesis is proposed:…”
Section: Investigating the Relationship Between Family Incivility And...mentioning
confidence: 85%
“…Internet addiction is positively correlated with stress and cyberbullying (Chu, 2023). Cyberbullying also is moderately correlated with depression (Balta et al, 2020;AlQaderi et al, 2023). Excessive social media consumption can also negatively impact a consumer's body image.…”
Section: Mental Illnesses Linked To Social Mediamentioning
confidence: 99%
“…Body image dissatisfaction (BID) is related to both depression and cyberbullying (Balta et al, 2020). A total of 33% of participants in the Schlüter (2023) explorative study found that there are similarities between cyberbullying and body shaming.…”
Section: Mental Illnesses Linked To Social Mediamentioning
confidence: 99%